The effect of acute and 7-days dietary nitrate on mechanical efficiency, exercise performance and cardiac biomarkers in patients with chronic obstructive pulmonary disease. Issue 6 (December 2018) - Beijers, Rosanne J.H.C.G.; Huysmans, Stephanie M.D.; van de Bool, Coby; Kingma, Boris R.M.; Verdijk, Lex B.; van Loon, Luc J.C.; Meex, Steven J.R.; Gosker, Harry R.; Schols, Annemie M.W.J.
Summary: Background & aims: Many COPD patients have a reduced exercise capacity and mechanical efficiency and are at increased cardiometabolic risk. This study aimed to assess acute and 7-days effects of dietary nitrate on mechanical efficiency, exercise performance and cardiac biomarkers in patients with COPD. Methods: This double-blind, randomized cross-over placebo controlled trial included 20 mild-to-moderate COPD patients (66.6 ± 7.5 years) with moderate exercise impairments and decreased mechanical efficiency, normal BMI (26 ± 3 kg/m 2 ) but high prevalence of abdominal obesity (83.3%). Subjects were randomly allocated to the treatment order of 7 days sodium nitrate ingestion (∼8 mmol/day) and 7 days placebo (NaCl solution) or vice versa, separated by a washout period. Before (Day-1) and after (Day-7) both intervention periods resting metabolic rate and the metabolic response during submaximal cycle ergometry, cycling endurance time, plasma nitrate and nitrite levels, cardiac plasma biomarkers (e.g. cardiac troponin T, Nt-proBNP and creatinine kinase) and blood pressure were measured. Subsequently, gross, net and delta mechanical efficiency were calculated. Results: Plasma nitrate and nitrite concentrations increased at Day-1 and Day-7 after sodium nitrate but not after placebo ingestion. Systolic and diastolic blood pressure did not change following nitrate ingestion. Furthermore, no differences were observed in gross, net, and delta mechanical efficiency during submaximal exercise, cycling endurance time and cardiac biomarkers between nitrate and placebo on Day-1 and Day-7. Meta-analysis of all available studies in COPD also showed no beneficial effect of beetroot juice on systolic and diastolic blood pressure. Conclusion: Acute as well as 7-days sodium nitrate supplementation does not modulate mechanical efficiency, blood pressure or cardiac biomarkers in mild-to-moderate COPD patients.